Hypervalent iodine-mediated cyclization of bishomoallylamides to prolinols - Butt, Smaher E.; Kepski, Konrad; Sotiropoulos, Jean-Marc; Moran, Wesley J. (Beilstein Journal of Organic Chemistry, 2024)
A change in mechanism was observed in the hypervalent iodine-mediated cyclization of N-alkenylamides when the carbon chain between the alkene and the amide increased from two to three atoms. In the latter case, cyclization at the amide nitrogen to form the pyrrolidine ring was favored over cyclization at the amide oxygen. A DFT study was undertaken to rationalize the change in mechanism of this cyclization process. In addition, reaction conditions were developed, and the scope of this cyclization studied.
Keywords: cyclization; DFT; hypervalent iodine; mechanism; proline